POST SECTIO CAESARIAN CHORIOCARCINOMA RESISTED TO COMBINE CHEMOTHERAPY - Ketut Suwiyoga, I Gde Sastra Winata, (E-Journal Obstetric & Gynecology Udayana, 2014)
Reported a case, 20 years old women diagnose with choriocarcinoma stage II with bidelfis uncials uterine, complained abnormal vaginal bleeding after 2 months post sectio caesaria. Done curettage with Anatomy Pathology examination result are rest pregnancy products. Two weeks after curettage, patient still complained vaginal bleeding. On physical examination found uterine enlargement appropriate 16-18 weeks, soft consistency. Positive pregnancy test with serum ?-hCG > 1500 mIU/ml. With ultrasonography seen duplex uterine, smaller at left uterine, at right uterine seen hypo-hyper echoic mass size 4x4 cm, was concluded as rest intrauterine pregnancy product and uterine duplex. After that was curettage with Anatomy pathology, the result is looks like choriocarcinoma. Patient was given combine chemoteraphy with Etoposide, Methotrexate (MTX), Actinomycin D (ACD), Cyclophosphamide, Oncovine (EMACO). After EMACO 3 series, the forth was delayed 1 month with increasing serum ?-hCG 38,43 mIU/ml. So this patient was diagnose with choriocarcinoma stage II post EMACO chemoteraphy 3 series (chemoresisten). Continued with hysterectomy supravaginal ( resection right delfis uterine) and give the EMACO 4th series. serum ?-hCG level was decrease to 0 mIU/ml after the EMACO 4th series. After the second EMACO the serum ?-hCG level also 0 mIU/ml, so we conclude this patient was remission.